Magnetic Mineralogical Approach for the Exploration of Gas Hydrates in the Bay of Bengal - Badesab, Firoz; Dewangan, Pawan; Gaikwad, Virsen; Kars, Myriam; Kocherla, Muralidhar; Krishna, Kolluru S.; Sangode, Satish J.; Deenadayalan, Kannan; Kumar, Pushpendra; Naikgaonkar, Omkar; Ismaiel, Mohammad; Khan, Aarbaz (My University, 2019)
We evaluate the environmental magnetic, geochemical, and sedimentological records from three sediment cores from potential methane‐hydrate bearing sites to unravel linkages between sedimentation, shale tectonics, magnetite enrichment, diagenesis, and gas hydrate formation in the Krishna‐Godavari basin. Based on downcore rock magnetic variations, four sedimentary magnetic property zones (I–IV) are demarcated. A uniform band of enhanced magnetic susceptibility (zone III) appears to reflect a period of high‐sedimentation events in the Krishna‐Godavari basin. Highly pressurized sedimentary strata developed as a result of increased sedimentation that triggered the development of a fault system that provided conduits for upward methane migration to enter the gas hydrate stability zone, leading to the formation of gas hydrate deposits that potentially seal the fault system. Magnetic susceptibility fluctuations and the presence of iron sulfides in a magnetically enhanced zone suggest that fault system growth facilitated episodic methane venting from deeper sources that led to multiple methane seepage events. Pyrite formation along sediment fractures resulted in diagenetic depletion of magnetic signals and potentially indicates paleo sulfate‐methane transition zone positions. We demonstrate that a close correlation between magnetic susceptibility and chromium reducible sulfur concentration can be used as a proxy to constrain paleomethane seepage events. Our findings suggest that the interplay between higher sedimentation events and shale tectonism facilitated fluid/gas migration and trapping and the development of the gas hydrate system in the Krishna‐Godavari basin. The proposed magnetic mineralogical approach has wider scope to constrain the understanding of gas hydrate systems in marine sediments.
Keywords: Magnetic susceptibility; Rock magnetism; Sedimentation; Magnetic mineralogy